2011
DOI: 10.1097/mcp.0b013e3283455c0b
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary infectious diseases in patients with primary immunodeficiency and those treated with biologic immunomodulating agents

Abstract: A wide array of bacteria, viruses, fungi and protozoa may cause severe pulmonary infectious diseases in patients with primary immunodeficiency and patients on treatment with anti-TNF and anti-CD20 drugs. Knowledge of the association of certain microbial agents with specific immune disturbances is of great clinical interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Anti-TNF is currently being used to treat human inflammatory and autoimmune diseases, for example, rheumatoid arthritis. Use of this drug has been associated with decreased immune responses to a variety of pathogens [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-TNF is currently being used to treat human inflammatory and autoimmune diseases, for example, rheumatoid arthritis. Use of this drug has been associated with decreased immune responses to a variety of pathogens [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis and other bacterial diseases, together with influenza, as well as diseases caused by respiratory syncytial viruses, human metapneumovirus, parainfluenza virus, adenoviruses and coronaviruses, can cause life threatening conditions in healthy people. Even otherwise harmless infections can cause complications in patients with pre-existing lung diseases such as asthma, COPD, bronchiectasis, cystic fibrosis, or primary immunodeficiencies, and other conditions that alter immunologic mechanisms against microbial invasion [229]. Susceptibility to infection as well as onset, duration and severity of symptoms is controlled by dynamic and patient-specific host-microbe interactions which, in addition to the rise in antibiotic resistance, has contributed to the difficulty of developing effective treatments [230][231][232].…”
Section: Pulmonary Infectious Diseasementioning
confidence: 99%
“…The presently available data suggest a subtle increase in the risk of infection in association with rituximab. However, concomitant immunosuppressive therapies and disease‐associated immune dysregulation make the causal attribution of infections problematic: A meta‐analysis in patients with rheumatoid arthritis reported that the overall odds ratio for serious infections under rituximab was not significantly increased (OR 1.45; 95% CI: 0.56‐3.73), and in another meta‐analysis of rituximab utilisation in clinical practice, anti‐CD20 therapy was associated with a significantly lower odds of serious infections relative to other biologics …”
Section: Depletion Of Cd20+ B Cellsmentioning
confidence: 99%